White light emission from sol-gel derived gamma-Y2Si2O7 nanoparticles - ERDEM, MURAT (ELSEVIER SCIENCE SA, 2015)
We report the generation of wideband white light with a spectrum ranging from 400 to 800 nm obtained from sol-gel derived gamma-Y2Si2O7 nano powders with average particle size under 100 nm when excited with the 803.5 nm emission of a laser diode. The white light intensity was found to increase with decreasing environment pressure and increasing laser pumping power. The International Commission on Illumination coordinates were found to be x = 0.3408 and y = 0.3100 under 803.5 nm excitation. These values lie in the yellowish region and correspond to color temperature values of 5030 K with a color rendering index of 85. The illuminance value was found to be 1456 lux. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Yttrium silicate; White light; Sol-gel; UP-CONVERSION; DOPED Y2SI2O7; NANO-POWDERS; NANOCRYSTALS; NANOPOWDERS; PHOSPHORS; Y2SIO5